Filosofia, gênero e literatura no século XVIII: a figura feminina apresentada por Jean-Jacques Rousseau no romance filosófico Júlia ou A nova Heloísa - SOUSA , Francyhélia Benedita Mendes (2022)
This research aims to analyze the interdisciplinary relationship between Philosophy, Gender and Literature in the 18th century from the female figure presented by Jean-Jacques Rousseau (1712-1778) in the philosophical novel Julia or, the new Heloise (1761). This is a qualitative, exploratory and bibliographical research, which has been methodologically developed based on theoretical analysis, interdisciplinary critical-reflective approach and hermeneutic interpretation. The analysis follows three interpretative axes: the first is concerned with identifying the feminine space in society and in French literature of the pre-revolution eighteenth century; the second investigates the role of the female figure exercised by Julia in the Encyclopedic Novel and the third has the function of examining Rousseau's discourse based on the notions of human nature, virtue and social function that underlie the female figure in that work, as well as examining the historical and novel representation of women from the notions of “Gender” and “Sex” worked on in the Century of Enlightenment. We found that, in general terms, the work proposes reflections on the relationship between nature, society, morals and politics from the bourgeois drama presented in a collection of letters, centered on the love lived by Júlia d'Etange, a young family member aristocrat and her tutor, the humble Saint-Preux and disapproved of by the girl's father, Baron d'Etange, both fictional characters from the small town of Clarens. The protagonists of a plot that confronts feeling, reason and virtue, the couple of lovers in the novel, reveal not only the portrait of human passions, but also the framework of the society idealized by Rousseau, by converging elementary concepts and conceptions of his thought. Based on the suggested bibliography, we conclude that Júlia is the key player in Rousseau's pedagogical-political project, whose objective is, in the foreground, in the catharsis of the passions and desires of a corrupt society, reaching, in the last plan, the moral elevation of individuals – both from the characters of the novel, and mainly from the readers, who are used to immediate pleasures, while getting used to contemplating the daily exercise of virtue, start to want to resemble Julia and to be more virtuous. Therefore, Julia or the new Heloísa is not just a moral role model who is limited to a virtuous female figure. But, in the final analysis, Júlia and the new Heloísa deal with a pedagogical-political model that aims at a new political organization, as well as, in the epistemological order, it aims to reconcile the conflict between nature and culture.